Using of EOQ and EPQ Methods in Minimizing Inventory Cost of Crude Palm Oil - Sari, Linda Kumala; Dur, Sajaratud; Husein, Ismail (UIN Sumatera Utara, 2020)
Excess or lack of inventory that is too large is a problem that can trigger increased costs so that companies do not get the benefits they should. The purpose of this study is to minimize the cost of inventories of crude palm oil using the EOQ (Economic Order Quantity) method and EPQ (Economic Production Quantity) methods at PT. Perkebunan Nusantara IV (Persero) Medan. From the results it is known that economic orders according to the EOQ method in 2017 amounted to 2.741,222 tons and in 2018 amounted to 2.825,927 tons. The difference in total inventory costs generated using the EOQ method and company conditions in 2017 amounted to Rp71.605.439.976,17 and in 2018 amounting to Rp60.884.174.907,3. The optimal amount of production (EPQ) in 2017 and 2018 was 146.226,147 tons. The difference in total inventory costs generated using the EPQ method and the condition of the company in 2017 and 2018 amounted to Rp102.771.704.121,63.